Maintaining Material Handling Equipment at Direct Reduction Plant PT Krakatau Steel - Suryowidagdo, Harry; Basri, Mursyid Hasan (The Indonesian Journal of Business Administration, 2013)
Looking forward business situations, management  of PT Krakatau Steel (Tbk) including Direct Reducton Plant (DRP),  tries to increase employee productivity by streamlining the organization and letting position left by retired person empty, but on the  other side there is a generation gap between experienced existing personnel and new hired employee. Another aspect in DRP is increasing capacity by implementing Zero Reformer Process (ZR) and decreasing raw material handling stockyard which is used by new Blast Furnace (BF) project,  Decreasing person and increasing capacity may bring operational difficulties and not optimal in DR Plant  maintenance. To achieve productivity targets and avoiding operational and maintenance difficulties, there are two major possibilities, 1. Not outsourcing which are: keeping current  organization and contract scheme condition (do nothing), applying new organization structure which eliminating and merging some position, and operating without any outsource personnel. 2. outsourcing, which are: manpower contract for Operation & Maintenance (O&M)., maintenance service contract, full maintenance contract (include spare part) and Full O&M Contract. Each option is given the advantage, disadvantage and constraints including cost, risk and also  government regulations . To choose options, we use AHP process, comparimg each alternative with predicted cost and risk factor for each option. The result of the study brings Operation & Maintenance Contract (O&M) is the most suitable among options. Implementing this option may need preparation in reviewing existing contract and preparation in completing equipment data and procedures. This study took part in pellets raw material handling process which decision steps can also be applied to other location in DR Plant and possibility for whole factory. Keywords: maintenance , raw material handling, not optimal,  risk, AHP, outsourcing.